2015
DOI: 10.1097/iae.0000000000000576
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes for Optic Disk Pit Maculopathy After Vitrectomy

Abstract: Vitrectomy for macular detachment due to optic disk pit has good long-term success and results in an improvement in visual acuity. However, adjuvant techniques such as internal limiting membrane peel and temporal endolaser may not improve outcomes, nor does there seem to be a difference between short- and long-acting gases. Patients should be made aware that it can take more than a year and multiple surgeries to achieve foveal reattachment and that increased baseline central retinal thickness is a poor prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 32 publications
7
53
1
2
Order By: Relevance
“…Our results suggest that laser treatment does not aid in anatomical success. This is in keeping with previous studies that have shown similar anatomical outcomes with PPV without juxtapapillary laser photocoagulation for ODP [13, 19-22]. …”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Our results suggest that laser treatment does not aid in anatomical success. This is in keeping with previous studies that have shown similar anatomical outcomes with PPV without juxtapapillary laser photocoagulation for ODP [13, 19-22]. …”
Section: Discussionsupporting
confidence: 77%
“…However, this method of treatment has largely fallen out of favour because the location of laser treatment over the maculopapular bundle can cause significant visual field defects [10, 11, 13]. Our results suggest that laser treatment does not aid in anatomical success.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations